EVALUATION OF TIMELY PASSING PROGRAM DEPARTMENT OF INDONESIAN LANGUAGE EDUCATION UNIVERSITAS INDRAPRASTA PGRI - Ade Siti Haryanti (Nurul Jadid University, 2021)
This study describes the Evaluation of Graduate Program on Time at Universitas Indraprasta PGRI. The purpose of this study is to evaluate the program for graduating on time as a consideration for the Faculty of Indonesian Language Education to make policies regarding the accuracy of student graduation. This study uses a qualitative descriptive method with the evaluation model used is Countenance Stake. The results of this study are that the program graduated on time at the Department of Indonesian Language Education, Universitas Indraprasta PGRI to be actively carried out even though the results have not been maximized. This can be seen based on the pass rate of almost 78%. From the initial number of 404 students who signed a thesis KRS contract and passed as many as 314 students, the remaining 90 students were still thesis drafting. Based on the observation that starting from the Department, Lecturers, and Administration, they contribute to students to complete their thesis on time, so that there is no ratio of lecturers to the number of students.